The Flow Graph Usage for the Attenuation Correction of the Low-pass Sallen-Key Biquad in the Current Mode - Brtník, Bohumil; Matoušek, David (IEEE (Institute of Electrical and Electronics Engineers), 2016)
The second order Sallen-Key low-pass filter structures (so called biquads) in the voltage and the current mode have one common disadvantage. This is a decreasing of the attenuation at high frequencies, because active elements exhibit losses of the amplification. While some solutions for the voltage mode circuits have been already published, but this problem was not satisfactorily solved for circuits working in the current mode. Therefore, this article presents one of the possible solutions of this problem for circuits working in the current mode derived by graph method.
Použití grafu signálových toků pro korekci útlumu dolní propusti v proudovém módu
Keywords: current mode; voltage mode; voltage graph; current graph; biquad; low pass filter in Sallen-Key structure